Substitution of Theophylline Slow-Release Formulations According to the Rebate Contracts in the German Statutory Health Insurance - Weissenfeld, Jörn; Lüngen, Markus; Stock, Stephanie; Drabik, Anna; Gerber, Andreas (Arzneimittelforschung, 2009)
On the basis of the rebate contracts between individual statutory health insurance funds and pharmaceutical enterprises, the generic substitution of prescribed medications is economically attractive and is advocated for statutory health insurees in Germany. In addition to the drugs whose substitution can be considered to be uncritical, rebate contracts also include controversial substances such as the bronchodilator theophylline (CAS 58-55-9), which has a narrow therapeutic range and should only be substituted under certain conditions.The objective of this article was to check the safety of the substitution of theophylline by means of a comparative evaluation of bioequivalence studies carried out on theophylline slow-release preparations.A systematic literature search was carried out in the MEDLINE database. The search terms used were combinations of the following key words: theophylline, generics, bioequivalence, substitution, brand and non-brand. In addition, a manual search was performed in the reference lists of the relevant articles. Only articles that were published between January 1, 1988 and August 30, 2008 were to be included.Five studies conformed to the inclusion and exclusion criteria. Two of the studies came to the conclusion that the preparations analysed were bioequivalent. In the remaining three studies there was no bioequivalence found between the preparations and the reference product. Because of the heterogeneity of study outcomes no metanalysis could be performed.On the basis of the studies analysed the conclusion can be drawn that a theophylline slow-release preparation should only be substituted under close monitoring by a physician because of the many factors which can adversely affect serum levels, such as the narrow therapeutic range of the active ingredient, the patient’s metabolisation rate or the different galenics of the preparations. Nevertheless, the question remains as to whether the costs saved by the rebate contracts would not be significantly outweighed.
Keywords: Bioequivalence; CAS 58-55-9; Generic substitution; Rebate contracts; Theophylline